Impacto da Mastite bovina por Sthapylococcus aureus e Streptococcus agalactiae - Mesquita, Alan Andrade (2017)
Bovine mastitis is the most important disease in dairy herds worldwide, causing great health and economic losses to producers and industry, as well as having implications for public health due to the zoonotic potential. Considering the multifactorial aspect of this disease, the knowledge of the agents involved in its etiology, antimicrobial susceptibility profiles, its economic impact on the production and the risk factors involved in its occurrence has high importance for its control. The experiment was carried out in partnership with a dairy industry in the region of Lavras/South of Minas Gerais, which at that time had 306 milk supply properties. In the first study, the impact of bovine mastitis on milk production was evaluated. In order to calculate the production losses, the means of three BMSCC of the 306 properties, obtained at intervals of 15 days between the collections, were used, and losses were estimated through the linear regression equation y = -4.7908 + 0.0226x, where the variable "x" represents the BMSCC and “y” the estimates of milk percentage losses. The mean of BMSCC between the studied properties was 482,650 cells/mL, and 43,710 CFU/mL of milk for total bacterial counts (TBC), with 35.6% and 7.84% of the farms above of limits established by current legislation for BMSCC and TBC, respectively. The results showed that the average daily losses in production due to mastitis were 6.27%. In the second study, the prevalence of Staphylococcus aureus and Streptococcus agalactiae was evaluated, by means of microbiological analyzes of milk samples collected from bulk milk tanks, and their relation with the BMSCC, TBC and daily production. Additionally, the resistance profile of S. aureus (99) and S. agalactiae (93) strains to antimicrobials was evaluated by disc diffusion technique. Our results showed high prevalences of S. aureus (70.3%) and S. agalactiae pathogens (67.0%), and associations between BMSCC and the presence of S. aureus and S. agalactiae pathogens and between the TBC and the presence of S. agalactiae, demonstrating the negative interference of these pathogens in these milk quality aspects. High levels of resistance and multiresistance were observed for S. aureus and S. agalactiae in the st udied herds. In the third study, a case-control study was carried out involving 46 dairy farms, of which 30 were considered as cases (CCSt ≥ 700,000 cells/mL of milk) and 16 as controls (CCSt ≤ 200,000 cells/mL of milk). Sixteen qualitative and four quantitative variables were analyzed. The results showed that the main risk factors for high BMSCC were the presence of the pathogens S. aureus and S. agalactiae, non-use of pre and post-dipping, non-use of paper towel for drying teats, non-use herd monitoring by California Mastitis Tests (CMT) or individual SCC, absence of the milking line and the therapy of dry cows, and failures in hygiene of teats and udders before milking. Failures related to maintenance and use of milking equipment, including the application of manual pressure to milking assemblies, unregulated vacuum pressure in milking machine, loss of vacuum during milking, and maintenance failures of milking machine and bulk milk tank were also found as relevant risk factors. Moderate correlations were a lso observed between elevation of BMSCC and counts of S. aureus and S. agalactiae in the bulk milk tank and moderate correlation between counts of S. aureus and counts of S. agalactiae. Our results showed high levels of production losses and prevalence of S. aureus and S. agalactiae pathogens, with high scores of antimicrobial resistance in the studied herds. The risk factors for BMSCC ≥ 700,000 cells/mL of milk were related to failures in relation to the classic measures of control of bovine mastitis, emphasizing the importance of the same to improve milk quality and mitigate the losses caused by this disease to producers and industry.